Ordinance no. A-17, § 1, Wilbur, Washington Town Council, 1894 (preventing the concealed carry or discharge of firearms). - (:unkn) unknown (General Publisher, 1894)
If any person shall carry upon his person any concealed weapons, consisting of either a revolver or pistol or other fire arms, or any knife (other than an ordinary pocket knife), or any dirk or dagger, slung shot or metal knuckles, or any instrument by the use of which injury could be inflicted upon the person or property of another, within the corporate limits of the Town of Wilbur, they shall be deemed guilty of a misdemeanor and upon conviction thereof shall be fined not less than five (5) dollars nor more than One hundred dollars ($100.00) or imprisoned in the town calaboose not more than thirty (30) days, or by both such fines and imprisonment in the discretion of the court, provided that this section shall not apply to police officers and other persons whose duty it is to execute process or warrants, or make arrests.
--
Keywords: CARRY - CONCEALED